Usability, acceptance, and educational usefulness study of a new haptic operative dentistry virtual reality simulator. (June 2022) - Rodrigues, Pedro; Esteves, Artur; Botelho, João; Machado, Vanessa; Zagalo, Carlos; Zorzal, Ezequiel Roberto; Mendes, José João; Lopes, Daniel Simões
Highlights: A Virtual Reality system to assist operative dentistry learning. Dental cavities can be virtually performed according to simulated dental caries lesions. Free-hand interaction provides additional degrees of freedom and valuable geometrical information. A study on user acceptance with dentistry professionals is a valuable tool to assess the educational usefulness prior to exposing dental students to this simulator. Abstract: Background: Dental preclinical training has been traditionally centered onverbal instructions and subsequent execution on phantom heads and plastic training models. However, these present present limitations. Virtual Reality (VR) and haptic simulators have been proposed with promising results and advantages and have showed usefullness in the preclinical training environment. We designed DENTIFY, a multimodal immersive simulator to assist Operative Dentistry learning, which exposes the user to different virtual clinical scenarios while operating a haptic pen to simulate dental drilling. Objective: The main objective is to assess DENTIFY's usability, acceptance, and educational usefulness to dentists, in order to make the proper changes and, subsequently, to test DENTIFY with undergraduate preclinical dental students. Methods: DENTIFY combines an immersive head mounted VR display, a haptic pen in which the pen itself has been replaced by a 3D printed model of a dental turbine and a controller with buttons to adjust and select the scenario of the simulation, along with 3D sounds of real dental drilling. The user's dominant hand operated the virtual turbine on the VR-created scenario, while the non-dominant hand is used to activate the simulator and case selection. The simulation sessions occurred in a controlled virtual environment. We evaluated DENTIFY's usability and acceptance over the course of 13 training sessions with dental professionals, after the users performed a drilling task in virtual dental tissues. Results: The conducted user acceptance indicates that DENTIFY shows potencial enhancing learning in operative dentistry as it promotes self-evaluation and multimodal immersion on the dental drilling experience. Conclusions: DENTIFY presented significant usability and acceptance from trained dentists. This tool showed to have teaching and learning (hence, pedagogical) potential in operative dentistry.